A Cosmological Scaling Relation for Describing the Late Time Dynamics - Gerardo Cristofano; Orlando Luongo (Advances in High Energy Physics)
A scaling relation between mass and minimal information of a given system is inferred from primordial black holes. Extending its validity, it is possible to describe different stages of the universe evolution. Particularly, the broad interest on matching the scaling law, from early to late redshift regimes, may suggest the mechanism to relate quantum and classical aspects of gravity. Under this hypothesis, the scaling relation is interpreted as a thermodynamic modification able to describe the cosmological dynamics at late times. In this scheme, dark energy emerges, as a consequence of assuming the validity of our scale relation. The corresponding equation of state reduces to a cosmological constant at early times and evolves in terms of the apparent horizon at late times.